2020
DOI: 10.21203/rs.3.rs-16460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A retrospective study of acral melanoma that happened on foot

Abstract: Methods: The aim was to investigate the epidemiological, clinical, and prognostic features of acral melanoma (AM) that occurred on foot, and to provide associated data for further study. A retrospective study was performed on patients with malignant melanoma (MM) who were treated in our hospital from January 2015 to January 2019. The tumor site was screened by foot. Basic data (e.g., gender, age, occupation, tumor location and etiology) of eligible patients, tumor-related data (such as tumor thickness, lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…Benign aMPPLs, instead, were slightly prevalent at hypothenar–metacarpal surfaces of palms, and clearly prevalent on the plantar arch of soles. These data show that there is essentially no difference between weight-bearing/non-weight-bearing areas of the soles in terms of melanoma development, which is in line with recent literature data that excluded a causative role of walking barefoot [ 16 , 17 , 18 , 46 , 47 , 48 ]. As per palmar melanoma, reports of a trauma occurrence are too very few to derive conclusions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Benign aMPPLs, instead, were slightly prevalent at hypothenar–metacarpal surfaces of palms, and clearly prevalent on the plantar arch of soles. These data show that there is essentially no difference between weight-bearing/non-weight-bearing areas of the soles in terms of melanoma development, which is in line with recent literature data that excluded a causative role of walking barefoot [ 16 , 17 , 18 , 46 , 47 , 48 ]. As per palmar melanoma, reports of a trauma occurrence are too very few to derive conclusions.…”
Section: Discussionsupporting
confidence: 91%
“…We did not detect any difference in sex distribution for PP melanoma cases (51%F/49%M); this trend is, however, in line with some retrospective studies on acral melanoma patients, reporting distribution of 54%/46%M [ 46 ] and 49%/51% [ 48 ], while previous monocentric studies showed a slight female or male prevalence (e.g., M:F = 1:1.86 [ 3 ], M:F = 1:1.6, [25 M:F = 1:1.9,12 F:M = 1:1.08,26 and M:F = 1:1.712). Precisely, a similar sex distribution was found in patients with cases of early melanoma of the body, in the context of retrospective studies on atypical melanocytic lesions [ 30 , 49 ].…”
Section: Discussionsupporting
confidence: 90%